Fertility and Hatchability in Goose Eggs: A Review - Salamon , Attila (International Journal of Poultry Science, 2020)
Two species of geese were domesticated from the waterfowl belonging to the Anatidae family, the Greylag goose (Anser anser) and the Swan goose (Anser cygnoides), which became the ancestors of most domestic geese all over the world. The rapid increase in goose production and the demand for day old goslings in the last century required improvements in breeding, nutrition, reproduction and management. This review focuses on the reproduction of geese with particular emphasis on two determining factors of artificial incubation, the fertility and hatchability of goose eggs. The first part of this review presents the factors that affect fertility and the latest ideas offering better performance in this regard. The second part of the review discusses three groups of factors influencing hatchability: breeder factors, egg factors and incubator/hatcher factors. Numerous studies were conducted in several topics with regards to goose egg hatchability in the last two decades, which are collected and discussed here. The third part discusses possibilities for future advances in relation to fertility and hatchability of goose eggs.